PROBLEMS IN THE USE OF DIGITAL TECHNOLOGIES IN IMPROVING THE QUALITY OF HOUSEHOLD SERVICES - Yerejepova Bibisara Abibullaevna (Modern American Journals, 2025)
This article analyzes the relevance of the digital economy, the state of the household services sector in the Republic of Karakalpakstan, and the challenges in implementing digital technologies. Based on this, modern approaches, proposals, and recommendations will be developed.
Keywords: digital economy, household services, digitalization, infrastructure, literacy, quality of services